ETS-1 in tumor immunology: implications for novel anti-cancer strategies - SiYu Wang; Lei Wan; XiaoJun Zhang; HaoXiang Fang; MengYu Zhang; Feng Li; DaWei Yan (Frontiers in Immunology)
ETS-1, a key member of the Erythroblast Transformation-Specific (ETS) transcription factor family, plays an important role in cell biology and medical research due to its wide expression profile and strong transcriptional regulation ability. It regulates fundamental biological processes, including cell proliferation, differentiation, and apoptosis, and is involved in tumorigenesis and metastasis, promoting malignant behaviors such as angiogenesis, matrix degradation, and cell migration. Given the association between ETS-1 overexpression and the aggressive characteristics of multiple malignancies, it represents a promising therapeutic target in cancer treatment. This study aims to systematically analyze the role of ETS-1 within the tumor immune microenvironment, elucidating its mechanisms in cancer initiation, progression, and metastasis. It also investigates the differential expression of ETS-1 across tumor tissues and adjacent normal tissues, exploring its potential as a molecular marker for tumor diagnosis and prognosis.